2017
DOI: 10.13057/tropdrylands/t010205
|View full text |Cite
|
Sign up to set email alerts
|

Population dynamics and performance of exotic versus indigenous chicken population in the selected districts of North Western Amhara, Ethiopia

Abstract: Abstract. Sisay T, Alemayehu K, Wuletaw Z. 2017. Population dynamics and performance of exotic versus indigenous chicken population in the selected districts of North Western Amhara,. Chicken in Ethiopia contributes, respectively, 98.5% and 99.2% of the national egg and chicken meat production. The total chicken population is estimated to be 56.87 million of which 95.86, 2.79 and 1.35% are indigenous, crossbred and exotic breeds, respectively. The objective of this paper was to quantify the population dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
(13 reference statements)
0
2
0
Order By: Relevance
“…Depending on the available scavenging feed resources in the area, the flock size under this system ranges from 10-50 chickens (Habte et al, 2017). Sisay et al, (2017) studied research on population dynamics and performance of exotic versus indigenous chicken population in the selected districts of North Western Amhara, Ethiopia. Under their result, they concluded that; about 91.12% of respondents used the backyard chicken management system in the studied area, whereas, 8.89% of smallholder farmers kept their chicken by the semi-intensive management system.…”
Section: Free-range Chicken Rearing Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on the available scavenging feed resources in the area, the flock size under this system ranges from 10-50 chickens (Habte et al, 2017). Sisay et al, (2017) studied research on population dynamics and performance of exotic versus indigenous chicken population in the selected districts of North Western Amhara, Ethiopia. Under their result, they concluded that; about 91.12% of respondents used the backyard chicken management system in the studied area, whereas, 8.89% of smallholder farmers kept their chicken by the semi-intensive management system.…”
Section: Free-range Chicken Rearing Systemmentioning
confidence: 99%
“…In most developing countries rural poultry plays a significant role in improving the nutritional status, income, food security, and livelihood of many smallholders (Zewdu et al, 2013). Ethiopia ranks first in Africa and the tenth in the world in livestock production, which plays important socioeconomic roles for the rural poor (Fessiha et al, 2010;Sisay et al, 2017).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%